2003
DOI: 10.1021/cm034341y
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation Chemistry and Bioapplications of Semiconductor Box Nanocrystals Prepared via Dendrimer Bridging

Abstract: A new strategy, dendrimer bridging, is developed for simultaneous formation and functionalization of biocompatible and bioaccessible semiconductor box nanocrystalssa dendron box around each colloidal semiconductor nanocrystal. CdSe plain core or CdSe/ CdS core/shell nanocrystals coated by a monolayer of organic dendron ligands (dendron nanocrystals) with hydroxyl groups as the terminal were chosen as the starting systems because of their potential biocompatibility and proven stability. A generation-two (G2) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
134
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 28 publications
4
134
1
Order By: Relevance
“…The DHLA-PEG ligand, however, afforded aqueous solutions of QDs which did not aggregate or bind protein in serum, giving a total HD of 8.7 nm ( Figure 1D). This is much smaller than the sizes reported for other QDs used in vivo, which range from about 15 to 30 nm in buffer, and include ligand spheres composed of polymers, 6 proteins, 7 cross-linked structures, 8 or multilayered combinations of ligands. 9 Any additional or non-specific protein binding, generally not well characterized in the literature, would further increase the effective sizes of these QD probes in vivo.…”
mentioning
confidence: 73%
“…The DHLA-PEG ligand, however, afforded aqueous solutions of QDs which did not aggregate or bind protein in serum, giving a total HD of 8.7 nm ( Figure 1D). This is much smaller than the sizes reported for other QDs used in vivo, which range from about 15 to 30 nm in buffer, and include ligand spheres composed of polymers, 6 proteins, 7 cross-linked structures, 8 or multilayered combinations of ligands. 9 Any additional or non-specific protein binding, generally not well characterized in the literature, would further increase the effective sizes of these QD probes in vivo.…”
mentioning
confidence: 73%
“…The conjugation of biomolecules with QDs has been achieved, as a rule, through covalent bonds using functional groups (linkers) on the QD surface (Gerion et al, 2001;Parak et al, 2002;Wolcott et al, 2006) or with the help of electrostatic interaction between QDs and biomolecules in self-essembled cases (Clapp et al, 2004;Ji et al, 2005;Torchynska 2009a). The essential set of publications related to the study of QD bioconjugation using PL spectroscopy revealed that the PL intensity of QDs decreased (Guo et al, 2003;Ji et al, 2005;Torchynska et al, 2009a;Vega Macotela et al, 2010) or increased (Torchynska et al, 2009a;Torchynska et al, 2009b) owing, as supposed, to the energy exchange between QDs and biomolecules. The shape of PL spectra of these bioconjugated QDs was not changed (Guo et al, 2003;Ji et al, 2005;Torchynska et al, 2009a;Torchynska et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The optical properties, characterized by their UV-Vis and PL spectra, of the CdSe/ZnS core-shell dendron-nanocrystal aqueous solutions in a sealed vial remained the same over two years stored on the shelf under room light and ambient conditions. Judging by the PL quantum yield and solubility, CdSe/ZnS core-shell dendron-nanocrystals were significantly more stable than CdSe/CdS core-shell dendron-nanocrystals studied previously [9][10][11] The CdSe/ZnS core-shell dendron-nanocrystals achieved good solubility in the common biological buffers such as PBS buffer solutions, acetic buffer solutions and Tris buffer solutions, and 2M NH 4 Ac solution. In strong chemical conditions, such as in 1 M HCl or 3% H 2 O solution, the dendron-nanocrystals survived for about 5min.…”
Section: Characterization Of the Cdse/zns Dendron-nanocrystalsmentioning
confidence: 82%